Farmsteads and funerary sites : the M1 junction 12 improvements and the A5-M1 link road, Central Bedfordshire : archaeological investigations prior to construction, 2011 & 2015-16 - Brown, Jim (Archaeopress Archaeology, 2020)
Extensive excavations by MOLA (Museum of London Archaeology) near Houghton Regis and Toddington, in south Central Bedfordshire, provide a detailed multi-period dataset for regional and national comparison. Evidence ranges from middle/late Bronze Age pits to medieval settlements.